A Comparative Study of Integrated Crop Management System vs. Conventional Crop Management System for Cotton Yield and Fiber Quality With Respect to Fruiting Position Under Different Soil Fertility Levels - Zhang, Xinyue; Yang, Hongkun; Snider, John L.; Zahoor, Rizwan; Iqbal, Babar; Chen, Binglin; Meng, Yali; Zhou, Zhiguo (Frontiers in Plant Science, 2018)
In order to increase cotton productivity and optimize fiber quality on limited arable land, an integrated crop management system (ICMS), which combined with some optimal management practices, is projected to replace the conventional crop management system (CCMS) for cotton production in the Yangtze River valley. The seedcotton yield and fiber quality with respect to fruiting position under ICMS and CCMS were investigated in 2012 and 2013 in two fields differing in soil fertility. Reduced bolls on fruiting branches 1-10 (FB1-10) and at fruiting position 1-2 (FP1-2) on FB11-15 could not be fully compensated by increased bolls on FB16+ under CCMS, resulting in more seedcotton yield under ICMS relative to that under CCMS. Fiber at majority fruiting positions under CCMS were longer and stronger than those under ICMS, but CCMS increased the contribution of bolls on FB11+ to the cotton yield, which overall resulted in no significant change in fiber length and strength by management system at field level. The number of bolls at FP1-2 on FB1-5 under CCMS while the number of bolls on FB1-5 and at FP1-2 on FB1-5 were not significantly changed by soil fertility, resulting in diminished yield difference in soil fertility among ICMS relative to that of CCMS. The high soil fertility significantly increased seedcotton yield relative to low soil fertility, which was attributed to more number of bolls on FB11+ and higher seedcotton weight per boll at all fruiting positions. High soil fertility field not only recorded superior fiber quality on FB11+, but also increased the contribution of these bolls to the cotton yield relative to those in the low soil fertility field, resulting in no significant change in overall fiber quality among soil fertility. These findings demonstrate that by combining optimal management practices on infertile soils ICMS could minimise the yield differences due to soil fertility without sacrificing fiber quality.